Expression profiling of Aldh1l1‐precursors in the developing spinal cord reveals glial lineage‐specific genes and direct Sox9‐Nfe2l1 interactions. Issue 9 (10th July 2013) - Molofsky, Anna V.; Glasgow, Stacey M.; Chaboub, Lesley S.; Tsai, Hui‐Hsin; Murnen, Alice T.; Kelley, Kevin W.; Fancy, Stephen P.J.; Yuen, Tracy J.; Madireddy, Lohith; Baranzini, Sergio; Deneen, Benjamin; Rowitch, David H.; et al.
<x xml:space="preserve">Abstract</x> Developmental regulation of gliogenesis in the mammalian CNS is incompletely understood, in part due to a limited repertoire of lineage‐specific genes. We used Aldh1l1‐GFP as a marker for gliogenic radial glia and later‐stage precursors of developing astrocytes and performed gene expression profiling of these cells. We then used this dataset to identify candidate transcription factors that may serve as glial markers or regulators of glial fate. Our analysis generated a database of developmental stage‐related markers of Aldh1l1+ cells between murine embryonic day 13.5–18.5. Using these data we identify the bZIP transcription factor Nfe2l1 and demonstrate that it promotes glial fate under direct Sox9 regulatory control. Thus, this dataset represents a resource for identifying novel regulators of glial development.